PENINGKATAN KETERAMPILAN MEMBACA PUISI MELALUI PENGGUNAAN MEDIA AUDIO VISUAL BAGI PESERTA DIDIK KELAS II SD NEGERI REJOSARI 01 KOTA SEMARANG SEMESTER 1 TAHUN AJARAN 2023/2024 - Ratnaningsih, Maulida Ulfa; Fajriyah, Khusnul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to describe: (1) the process of learning to read poetry using audio-visual media; (2) improving poetry reading skills through audio-visual media in Indonesian language learning for class II students at SDN Rejosari 01 Semarang City Semester 1 of the 2023/2024 academic year. The subjects of this research were class II students at SDN Rejosari 01 Semarang City, totaling 28 children. The object of this research is the poetry reading skills of class II students at SDN Rejosari 01. Data collection techniques use observation, tests and documentation. Data analysis techniques use qualitative data and quantitative data. This research is classroom action research. One class is taken by 28 students. The data collection method was carried out using written tests and observation sheets. Class action planning in this plan is designed in 2 cycles. Each cycle consists of planning, implementing actions, observing and reflecting. Based on the research results, it can be concluded that (1) the process of learning to read poetry with audio-visual media for class II students at SDN Rejosari 01 was carried out according to procedures established by the researcher (2) there was an increase in student learning outcomes and the percentage of completion in reading poetry with media. audio visual . The average score obtained for cycle 2 was 88,26, with 25 or (89%) students completing and 3 or (11%) students not completing. Overall the increase in average score from pre-cycle to cycle 2 was 20,37.